Analisis Efektivitas Penerapan Keselamatan dan Kesehatan Kerja (K3) pada Kantor Pencarian dan Pertolongan Kelas B Jambi - Siska Vermina; Muhammad Firzah (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
Occupational Safety and Health (OHS) is a crucial aspect in supporting the smooth and successful implementation of the National Search and Rescue Agency (Basarnas), particularly in high-risk search and rescue operations. The Search and Rescue Office Class B of Jambi, as a Basarnas technical implementation unit, is required to implement an OHS system effectively to protect personnel safety and minimize the risk of workplace accidents. However, in practice, various challenges remain that could potentially impact the effectiveness of OHS implementation in the workplace. Therefore, this study aims to analyze the effectiveness of Occupational Safety and Health (OHS) implementation, identify the obstacles and barriers encountered, and formulate efforts to improve the effectiveness of OHS implementation at the Jambi Class B Search and Rescue Office. This study used a qualitative research method with a descriptive approach. The results indicate that OHS implementation at the Jambi Class B Search and Rescue Office has generally been quite effective. This is reflected in compliance with OHS Standard Operating Procedures (SOPs), the use of personal protective equipment (PPE) in operational activities, the implementation of OHS training, and the readiness of the emergency response system to support personnel safety. However, this study also identified several obstacles, including limited safety facilities and infrastructure, high operational intensity, and the need for increased consistency in OHS monitoring and evaluation. Therefore, efforts to improve the effectiveness of OHS implementation need to be undertaken through strengthening occupational safety culture, improving personnel competency and awareness, and optimizing OHS support facilities, infrastructure, and administrative systems.